Is there a Weed Shift in Roundup Ready Maize? (Poster Presentation at the 4th International Workshop on PMEM of Genetically Modified Plants, Quedlinburg, Germany, 2010) - Arnd Verschwele (Journal für Kulturpflanzen, 2011)
Weed effects of the use of glyphosate were investigated in a 6-years field study of continuous transgenic herbicide-resistant maize rotation (2003–2008). It was conducted at three sites in Germany which differed in terms of soil, climate, field history, and consequently initial weed spectrum. The studies focussed on the comparison between local herbicide standards and split applications of Roundup Ready (360 g L–1 glyphosate) applied at dosages of 1.5 + 1.5; 2 + 2 and 3 + 3 L ha–1 Roundup Ready.